(untitled) (Journal of Asian Development Studies, 2014)
This study applies Enders and Siklos’ (2001) procedure to test for the long-run asymmetric co-integrating relationship and Granger causality between Pakistani monthly money supply M2 and monthly equity index over the period June 1998 to December 2013. The empirical results suggest a long-run asymmetric co-integration relationship between the broadly defined money supply and equity index, indicating that the countercyclical monetary policies affect investors and corporations differently in different phases of business cycle. The empirical results further suggest that Pakistani equity investors are more responsive to contractionary than expansionary monetary policy measures. Thus, the Pakistani Central Bank countercyclical monetary policy is effective in influencing the equity markets. The empirical findings should be of special interest for the Central Bank in formulating and implementing its countercyclical monetary policy, for equity investors in designing their investment strategies, and for corporate executives to determine their optimal capital structures.